Autoreduction of cyanoferrate(III) ions in a polymer electrolyte membrane: all solid state electrochemical and spectroscopic investigations - Parthasarathy, Meera; Gopinath, Chinnakonda S.; Pillai, Vijayamohanan K. (Chemistry of Materials, 2006)
The effect of dielectric confinement on proton-coupled electron-transfer behavior and spectroscopic properties of cyanoferrate ions in a polymer electrolyte membrane (Nafion) has been investigated in an ``all-solid-state'' electrochemical cell, using techniques such as cyclic voltammetry, zero current chronopotentiometry, electrochemical impedance, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron spin resonance spectroscopy (ESR). From the above investigations, we found that cyanoferrate(III) ions undergo autoreduction in the ionomer matrix, for which a sulfonate-coupled mechanism has been proposed. This report demonstrates the effectiveness of the micellar interface in tuning the redox potential of the confined ions. A systematic analysis of the cyclic voltammetry and impedance data for the [Fe(CN)(6)](4)(-)- containing Nafion membrane enables the estimation of a standard rate constant for [Fe(CN) 6](4-) oxidation, k(o), as 5.44 x 10(-6) cm/s and a diffusion coefficient, D-o, as 1.3 x 10(-12) cm(2)/s. A similar calculation yields a value of 4.8 x 10(-12) cm(2)/s for the diffusion coefficient of protons and 9.1 x 10(-6) cm/s for the standard rate constant for hydrogen oxidation. The similarity in mass-transfer coefficients calculated for protons and [Fe(CN)(6)](4-) ions suggests a proton-coupled electron-transfer mechanism for the [Fe(CN)(6)](4-)/[Fe(CN)(6)](3-) couple. The results of the above investigations could have direct technological relevance for deciding catalyst materials having redox compatibility with the polymer electrolyte, especially in the preparation of catalyst-coated membranes (wherein the fuel-cell catalyst is directly coated onto the polymer membrane instead of on the carbon support).

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior